PENGARUH PENGGUNAAN METODE CERAMAH TERHADAP TINGKAT PEMAHAMAN PESERTA DIDIK DALAM PELAJARAN AGAMA KATOLIK DI KELAS VIII SMP NEGERI 2 KUPANG - Huler, Andreas Martinus; Dau, Yoseph Lodowik Deki; Oetpah, Dorince (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2023)
The purposes of this research are: 1) to find out how the description of the use of the lecture method in Catholic religion lessons and how the level of understanding of class VIII students at SMP Negeri 2 Kupang; 2) to find out whether there is an effect of using the lecture method on the level of understanding of class VIII students at SMP Negeri 2 Kupang. Data collection techniques in this study used questionnaires (questionnaires) and documentation, while data analysis techniques used descriptive statistical analysis and inferential statistical analysis. The results of this study indicate that the description of the use of the lecture method is in the good category (56.39%), also the level of understanding of students is in the good category (73.37%). In addition, there is an effect of the use of the lecture method in Catholic religion lessons on the level of understanding of students in class VIII SMP Negeri 2 Kupang, where the t value is 4.679, and the sig value is smaller than the alpha value (0.05).